2012
DOI: 10.1890/12-0188.1
|View full text |Cite
|
Sign up to set email alerts
|

Niche engineering reveals complementary resource use

Abstract: Abstract. Greater resource use by diverse communities might result from species occupying complementary niches. Demonstrating niche complementarity among species is challenging, however, due to the difficulty in relating differences between species in particular traits to their use of complementary resources. Here, we overcame this obstacle by exploiting plastic foraging behavior in a community of predatory insects common on Brassica oleracea plants in Washington, USA. These predators complemented one another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…2010, Gable et al. 2012). Consequently, our metric of diet breadth may have captured more subtle separation in predator feeding locations between specialist and generalists that were not captured by broader distinction within the habitat domain category.…”
Section: Discussionmentioning
confidence: 99%
“…2010, Gable et al. 2012). Consequently, our metric of diet breadth may have captured more subtle separation in predator feeding locations between specialist and generalists that were not captured by broader distinction within the habitat domain category.…”
Section: Discussionmentioning
confidence: 99%
“…In general, these experiments indicated that more diverse communities exhibited high productivity and a more efficient resource use compared to less diverse communities (Hooper et al 2005). Later, BEF experiments were extended to other communities and their complexity has increased to better discriminate the effects of individual species (identity effects) from the effects of partitioning in resource use among species (complementarity) (Gable et al 2012). Novel aspects of BEF research have also involved the analysis of realistic non-random species losses (Bracken et al 2008) and the exploration of trophic interactions (Aquilino & Stachowicz 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in predator-prey systems, for example, has shown that the diversity of the resource base can have considerable impacts on the biodiversity-ecosystem functioning relationship. In a system with predators feeding on aphids on collard plants, for example, coccinellid beetles forage on leaf edges while parasitoid wasps forage on leaf centers, leading to spatial complementarity and a positive relationship between predator diversity and aphid consumption10. However, when caterpillars are introduced to the system this complementarity is reduced because caterpillars chew holes in leaf centers (creating edges for coccinellids), and species identity effects become prevalent due to increased niche overlap between predators10.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach is to directly manipulate niche complementarity among consumers, and experimentally determine if greater complementarity promotes resource consumption910. Both of these approaches, however, require complex experimental designs that are often not practical for many systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation